Extraction of lignin from black liquor for application as loss circulation material in drilling mud - Wan Mohamed@Adnan, Wan Ahmad Ilham (2017)
Well exploration and drilling are the most expensive process in oil and gas industry. Some of the materials that are used plentiful during drilling process are lost circulation material (LCM). The materials are used to prevent the loss of drilling fluid into the natural or induced fracture. Black liquor (BL) are the liquid by-product of the kraft pulp process in the paper industry. This waste could be disastrous if release to natural water stream because it has a very high pH value. The valuable lignin contain in BL are abundant and it uses as LCM in drilling fluid is no stranger. In this research, the lignin extracted from BL will be used directly as LCM in drilling mud. The DOE Taguchi method are used during the extraction with two parameter level, types of acid used and two different pH value. The mass percent yield of the extracted lignin are increase as the pH value are lower. It is also proven that lower the pH value of acidic BL, the more yield the extracted lignin based on the analysis done on it physical properties done using FTIR.